Antipsychotic treatment: experiences of fully recovered service users. (4th May 2017) - Bjornestad, Jone; Davidson, Larry; Joa, Inge; Larsen, Tor Ketil; Hegelstad, Wenche ten Velden; Langeveld, Johannes; Veseth, Marius; Melle, Ingrid; Johannessen, Jan Olav; Bronnick, Kolbjorn
Abstract: Background : There is lack of long-term controlled studies evaluating treatment effects of antipsychotic medication. A complete investigation should include the service user perspective. Aims : To investigate experiences of clinically recovered service users of antipsychotic medications during and after a first episode of psychosis. Method : We used a thematic analytic approach within an interpretative-phenomenological framework. 20 clinically recovered service users were interviewed. Results : Themes: (1) Antipsychotic drugs reduce mental chaos during the acute phase, (2) Non-stigmatizing environments were perceived to increase chances of successful use, (3) Antipsychotic drugs beyond the acute phase – considered to compromise the contribution of individual effort in recovery, (4) Prolonged use – perceived to reduce likelihood of functional recovery, (5) Antipsychotic medication was considered as a supplement to trustful relationships . Conclusions : Acute phase antipsychotic treatment was mostly perceived as advantageous by this sample, who was in clinical recovery. However, costs were often seen as outweighing benefits beyond the acute stage. Findings clearly emphasize the need for a collaborative approach to be integrated across all phases of care. This study underscores the need to investigate sub-group differences with regard to long-term antipsychotic treatment.